Macao Soundscape as an Analysis Tool for Sound Quality Assessment - Pestana, Pedro; Barbosa, Alvaro; Estadieu, Gerald (Instituto Politécnico de Portalegre, 2022)
Macao SAR, China is one of the more densely-populated territories in the world, and as such necessarily struggles with Soundscape quality. Nonetheless, the territory has already been identified as a unique location for to function as a Soundscape living lab (Cordeiro et al., 2014), since it has a very small manageable area that includes many types of geographical varieties, from extremely high density urban areas to natural environments with dense vegetation highland or varied water front typologies. In addition, Macao has extremely wide multicultural population with a broad range of subjects that have diverse cultural perceptions and thresholds in regards to sonic cognition. The potential impact of this diversity has already been noticed in both tourism (To & Chung, 2019) and research (Chung et al., 2016). The concept of Soundscape itself is garnering increased awareness as a viable alternative to assess the quality of the sonic environment, of use to policy management and legislation, shown not only by the increasing numbers of scientific articles on the subject (Moscoso et al., 2018), but also by recent international standardisation efforts in measuring it (ISO,2018). In this talk we shall give a preliminary description and illustration of the Soundscape in a territory that is rich in diversity and has huge potential for citizen participation. This includes approaches like noise mapping, sound mapping, Soundwalks, grounded theory efforts for detailed descriptions of the environment and use of alternative objective metrics. We will describe how to use the richness of this gathered data in developing artificial-intelligence algorithms to autonomously assess and predict the evaluation of a given Soundscape based on recordings alone. This goal will alleviate the intense human effort in subjective assessment, and may prove to be an effective and substantial diagnostics tool in planning the soundscape for prospective built environments, functioning not only as an analysis and diagnostics tool, but as a design strategy for a sustainable sonic future.